Surgical Denervation of Spermatic Cord for Chronic Scrotal Content Pain: A Modified Technique - Ehab M. Ahmed,; Ahmed J. Alsayyad, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Microsurgical denervation of the spermatic cord has been described as a treatment modality for patients with chronic scrotal content pain. The aim of our study is to evaluate a modified technique by performing denervation of the spermatic cord without a surgical microscope in patients with chronic scrotal content pain as a simplified modality. This retrospective study included 20 patients who underwent denervation of spermatic cord without using surgical microscope for treatment of intractable chronic scrotal content pain. Post denervation pain was assessed 6 months after the surgery. Twelve (60%) patients reported complete alleviation of the symptoms, four (20%) patients noticed more than 50% improvement in their symptom, two (10%) patients had less than 50% improvement, and two (10%) patients reported no changes in their complaint. In conclusion, denervation of the spermatic cord without using surgical microscope is simple and feasible and shows comparable results to microsurgical denervation in treating patients with chronic scrotal content pain. Further studies are needed to confirm the efficacy of this modality.